Japanese mutual funds before and after the crisis outburst: A style- and performance-analysis - Stephanos Papadamou; Nikolaos A. Kyriazis; Lydia Mermigka (International Journal of Financial Studies, 2017)
This paper investigates how mutual funds performed in Japan before and after the 2008 outburst of the global financial crisis, that is during the extension of an extraordinary unconventional monetary policy by the Bank of Japan. Style and performance analyses are employed in order to investigate whether active or passive management has been affected by unconventional times and to what extent. Evidence indicates that in four out of eight funds, asset selection presents a significant contribution to returns. The Selection Sharpe Ratios for sectoral and style analyses exhibit positive values added per unit of risk due to active management for the majority of our funds in the pre-Lehman default period. Nevertheless, none of them presents statistical significance according to the t-statistic. Moreover, over the post-Lehman default, only two out of eight funds achieved lower volatility levels and higher returns due to active management. A style drift to big capitalization stocks with low values of book to market ratio is to be held responsible for the outperformance. Overall, our findings imply that active management in a monetary easing environment does not add significant value to the mutual fund performance.
Keywords: E58; G11; G12; 330; style analysis; unconventional monetary policy; Japanese mutual funds